Gynaecological Laparoscopy: A Retrospective Evaluation of Associated Complications - Ali Buhur; Omer Unal (Clinical and Experimental Obstetrics & Gynecology)
Background: The aim of this study was to determine the rates of diagnostic and operative complications of gynecological laparoscopic procedures, and identify risk factors for the occurrence of these complications. Methods: This retrospective study included 680 women who underwent gynecological laparoscopy for benign indications between 01 July, 2015, and 01 September, 2020, at Kanuni Sultan Süleyman Training and Research Hospital. They were classified into diagnostic and operative laparoscopy groups. Laparoscopic entry and operative complications were thoroughly analyzed. Mean age, mean parity, history of previous surgery, operative time, amount of blood loss, complication rates, and length of postoperative hospital stay were compared. Results: There were significant differences between groups in terms of mean age, parity, history of previous surgery, duration of surgery, hemoglobin drop, length of surgery, and length of hospital stay (p < 0.001). Overall, 28 (4.11%) complications occurred of the total complications, 9 (1.32%) had arisen prior to the procedure or during the insertion of the abdominal trocars. Complications dramatically increased, particularly in gynecological laparoscopic procedures lasting longer than 110 minutes with a 68.5% sensitivity and 69.1% specificity. Conclusions: A direct relationship was observed between the duration of surgery and the complication rates. In this study, we found that problems dramatically increased, particularly in gynecological laparoscopic procedures lasting longer than 110 minutes. However, regardless of the type of laparoscopic procedure significant complications had arisen prior to the procedure or during the insertion of the abdominal trocars.